THE COMPARATIVE STUDY: THEOLOGICAL ANALYSIS OF TOLERANCE BETWEEN ISLAM DAN CHRISTIANITY TRADITIONS - Hamonangan, Ranto Praja (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
This paper discusses tolerance from Christianity and Islam perspective. What is tolerance: basis, limit, and example in the scripture—the research doing by bibliography approach. Books, journals, and scriptures are the resources. Hopefully, the results can provide a broader understanding of the theology and tolerance field. Thus these works can be used as references. Through discussion, it found that Christianity and Islam talk about tolerance. They tolerate others, even though there are some interpretations to interpret the scripture either in Christianity or Islam, but they are still open to others. Tolerance is a necessity that becomes an advantage to compete with each other in the pursuit of goodness.